The dead years - Burton, Jeffrey B. (Burton, Jeffrey B. Chicago K-9 Thriller., 2024)
"Siblings Cory and Crystal Pratt are still trying to get their lives together after a tragic accident which killed their parents years ago. The only thing that distracts them now is their jobs. With Crystal working as a newly minted detective at the Chicago Police Department and Cory owning a dog training academy with two human remains detection dogs of his own, their professional paths cross every now and then. Crime, and especially murder, in Chicago is nothing new, but when a string of killings happen that seem to be connected to a Netflix docuseries and its cast and crew, Cory and Crystal are called in to stop the number of bodies from piling any higher. But when the siblings start poking around the killer's business, the killer sets their sights on the pair . . . and particularly on Cory and his dogs! Will they be able to escape the fury of the serial killer or become the newest victims?"--Back cover.